Sustainable Development in India: Groundwater Irrigation, Energy Use, and Food Production (Routledge New Horizons in South Asian Studies, 2021)
This book explores and interrogates the food–water–energy nexus, arguably the most crucial factor in sustaining India’s economic development. The book sheds light on different experiences faced in states across India, including the consequences of electricity tariff reforms and related policies on irrigated agriculture. Part 1 focuses on the historical development of agriculture and social change in India, with special reference to the mode of responses and adaptations in social systems against the inherent low and erratic rainfall and resulting water stress in India during the pre-colonial period. Additionally, it investigates how colonial development destroyed social systems and discusses future development prospects. Part 2 discusses contemporary issues of agriculture and social change in India. A comprehensive examination of various important issues related to South Asian agricultural development in the past and in the present, this book will be a valuable reference for researchers of Asian development, sustainable development, environmental policy, South Asian Studies and Development Studies.